2022
DOI: 10.1186/s12939-022-01736-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of community and provider-driven social accountability interventions on contraceptive uptake in Ghana and Tanzania

Abstract: Background Social accountability, which is defined as a collective process for holding duty bearers and service providers to account for their actions, has shown positive outcomes in addressing the interrelated barriers to quality sexual and reproductive health services. The Community and Provider driven Social Accountability Intervention (CaPSAI) Project contributes to the evidence on the effects of social accountability processes in the context of a family planning and contraceptive programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…However, additional research is needed to understand if the WABA approach has contributed to increases in contraceptive uptake. Previous studies have shown mixed results regarding the implementation of similar approaches and improved health outcomes ( 33 36 ) . Additionally, given the limited adherence to community action plan activities that address structural challenges at the facility level, there may be limits in the extent to which this approach can be used to address broader health system improvements outside provider behavior and community engagement, particularly in low-resource settings ( 37 , 38 ).…”
Section: Perceived Effects Of the Community Engagement Approach On Fp...mentioning
confidence: 99%
“…However, additional research is needed to understand if the WABA approach has contributed to increases in contraceptive uptake. Previous studies have shown mixed results regarding the implementation of similar approaches and improved health outcomes ( 33 36 ) . Additionally, given the limited adherence to community action plan activities that address structural challenges at the facility level, there may be limits in the extent to which this approach can be used to address broader health system improvements outside provider behavior and community engagement, particularly in low-resource settings ( 37 , 38 ).…”
Section: Perceived Effects Of the Community Engagement Approach On Fp...mentioning
confidence: 99%
“…During CaPSAI, they implemented their social accountability process in districts where they did not have an active programme taking place. More details of the intervention (McMullen et al, 2022; Steyn et al, 2022; Steyn et al, 2020 (a); World Health Organization, 2021) and the role of the implementation teams in CaPSAI (Cordero et al, 2022) have been published elsewhere.…”
Section: The Capsai Project: How the Process Evaluation Fit Into The ...mentioning
confidence: 99%
“…The process evaluation data has been used to contextualise and understand the causal pathways explaining the main outcomes of CaPSAI (Steyn et al, 2022). Several manuscripts are being written up to report on these findings and will be published separately.…”
Section: Data Analysis Process – How Process Evaluation Data Were Ana...mentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive and analytic work on implementation is further complicated by the broad and interrelated set of outcomes that together facilitate change. Outcomes may include both routine health and service delivery outcomes [ 4 ], alongside changes in self-efficacy, social cohesion, trust, and responsiveness [ 5 ]. Even when the outcomes are delineated, it may be difficult to attribute them to a specific part of a multi-component intervention.…”
mentioning
confidence: 99%